The Effect of The Tangram Media Assited STAD Model on The Understanding Of Mathematics Concepts Of Flat Building Materials - Sari, Viainda; Mardiana, Tria; Purwandari, Septiyati (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the STAD model assisted by tangram media on the understanding of mathematical concepts in fourth grade students of SD Muhammadiyah Integratif Dukun, Magelang Regency.This research is a type of pre- experimental research with one group pretest-posttest design. The research was selected by saturated sampling. The samples taken were 19 students. The method of data collection is done by using a description test. The validity test uses the product moment formula, while the reliability test uses the Cronbach alpha formula which produces a reliability index of 0.924. Data analysis used parametric statistical techniques, namely the Paired Sample T-Test with the help of the SPSS for Windows version 25.00 program.The results of the analysis of the Data Test of Two Dependent Samples which were carried out using the Paired Sample T-Test with the t count > t table, namely 18.323 > 2.093 with the Asymp value. Sig. (2-tailed) 0.000 < 0.05. Based on the results of the analysis and discussion, there is a difference in the average score of the mathematical concept understanding test, namely the pretest average of 50.46, while the posttest average is 80.02. This shows that there is an effect of the STAD model assisted by tangram media on the understanding of the mathematical concept of flat shape material in fourth grade students of SD Muhammadiyah Integratif Dukun, Magelang Regency, Academic Year 2020/2021.